Central Serous Chorioretinopathy: Multimodal Imaging and Management Options - Prashanth G. Iyer; Stephen G. Schwartz; Jonathan F. Russell; Harry W. Flynn (Case Reports in Ophthalmological Medicine)
Central serous chorioretinopathy (CSCR) is an idiopathic maculopathy characterized by thickened choroid, retinal pigment epithelial detachment, and variable subretinal fluid. CSCR predominantly affects young men, with risk factors including corticosteroid use, the type A behavior pattern, and psychological stress. While usually self-limited with a good visual prognosis, recurrent and persistent CSCR can lead to outer retinal and/or retinal pigment epithelial atrophy, choroidal neovascularization, and visual loss. This article reviews current multimodal imaging and treatment options, which include observation, mineralocorticoid receptor antagonists, thermal laser photocoagulation, and off-label photodynamic therapy with verteporfin.